INCREASING STUDENT COMPUTER NETWORK COMPETENCY AT VOCATIONAL MIDDLE SCHOOL SMK DWI PANGGA BANDAR LAMPUNG - Aliy Hafiz; Ifo Wahyu Pratama; Verawati (Universitas Nahdlatul Ulama Lampung, 2021)
Computer networks were basis of development of communication technology. The relationship between one device and another makes it easier for humans to relate to one another. Computer network learning method through computer network training through basic theory and practice of network installation. The purpose of this activity is to provide training to participants regarding computer network configuration that has never been taught before, it is hoped that the training can improve the skills of participants. SMK Dwi Pangga is one of the private vocational schools in Bandar Lampung City, as an IT-based vocational school or one that manages the TKJ Department, it is proper to use computer networks as facilities and infrastructure in the teaching and learning process and service to students. but in reality it has not been implemented due to lack of understanding and not understanding the functions and advantages of a computer network. that is the reason why it is important to do this service at SMK Dwi Pangga.